Local allergic rhinitis: entopy or spontaneous response?. Issue 1 (December 2016) - Gelardi, Matteo; Guglielmi, Antonio; Iannuzzi, Lucia; Quaranta, Vitaliano; Quaranta, Nicola; Landi, Massimo; Correale, Mario; Sonnante, Annamaria; Rossini, Margherita; Mariggiò, Maria; Canonica, Giorgio; Passalacqua, Giovanni
Abstract Background The existence of a local allergic rhintis was proposed on the basis of the detection of nasal IgE in the absence of a systemic sensitization. Nevertheless, the significance of this phenomenon remains still unclear. We assessed the presence of mucosal nasal IgE in patients with ascertained allergic rhinitis, nonallergic rhinitis with inflammation and in healthy controls. Methods Consecutive patients with a well ascertained diagnosis (clinical history, skin prick test, specific IgE assay, nasal endoscopy, nasal cytology) underwent an immunoenzymatic measurement of specific IgE to grass, cypress, parietaria and olive in nasal scrapings. Results Fifteen patients with allergic rhinitis, 12 with non allergic rhinitis and 14 healthy subjects were studied. The patients with allergic and nonallergic rhinitis had higher nasal symptoms as compared to control subjects. Systemic sensitizatition (assessed by skin test and CAP-RAST) was obviously more frequent in allergic rhinitis, than in the other two groups. Allergen-specific nasal IgE could be detected in all groups (86, 7, 33, 3, and 50 % positive, respectively), even more frequently in the control group than in nonallergic rhinitis patients. No difference among allergens was identified. Out of the 26 non-allergic patients (non allergic rhinitis + controls) nasal IgE were positive in 11(42 %). Discussion According to the results, the presence of nasal IgE against allergens seems to be a non-specific phenomenon, since they can be detected also in non allergic rhinitis and in healthy subjects. Conclusion It can be hypothesized that the nasal IgE production represents a form of spontaneous immune response.